The effect of plum extracts and antioxidants on reduction of ethyl carbamate in plum liqueur - Jung, Sunghyeon; Lee, Hyunjun; Kim, Inhwan; Kim, Seongjae; Lee, Bokyung; Lee, Jihyun (Food science and biotechnology, 2024)
Stone-fruit liqueurs contain high contents of the carcinogen ethyl carbamate (EC). In this study, we investigated the effect of plum fruit extract and single antioxidants present in plum fruit extracts on the reduction in the EC content during the macerating process in a plum liqueur model system and authentic plum liqueur. 30% ethanol model plum liqueur treated with 0.2% plum extract showed the lowest EC content with 55% reduction rate after the macerating process compared to the content in the control. Interestingly, neither 0.1% ascorbic acid nor 0.1% p-coumaric acid lowered the EC contents in the model liqueur, while they decreased the EC contents in authentic plum liqueur. This was possibly attributed to the synergistic effect of the plum fruit phenolics with the ascorbic acid and p-coumaric acid antioxidants. Thus, plum extracts can be applied to plum liqueurs to reduce the rate of EC formation.